DESENVOLVIMENTO DE PODISUS NIGRISPINUS (DALLAS, 1851) (HEMIPTERA: PENTATOMIDAE) ALIMENTADO COM LAGARTAS DE DIATRAEA SACCHARALIS (FABRICIUS, 1794) (LEPIDOPTERA: CRAMBIDAE) - Vacari, A.m. [UNESP] (2022)
The aim of this study was to evaluate the biological aspects of Podisus nigrispinus (Dallas) fed on Diatraea saccharalis (Fabricius) caterpillars. The eggs (200) used for the trial were obtained from the mass rearing of the Laboratory of Biology and Insect Rearing of the Department of Plant Health, at FCAV/UNESP. The eggs were maintained in an acclimatized room (T = 25 ± 1° C, photophase = 12h and RH = 70 ± 10%), where the following parameters were evaluated: embrionary period and egg viability. When the nymphs reached the 2nd instar, the insects were individualized in Petri dishes, where the following parameters were evaluated: nymph viability, duration of the nymph period and weight of 5th instar nymph. In the adult stage, the insects were coupled in Petri dishes, where the following parameters were evaluated: preoviposition, oviposition and post oviposition periods; adult longevity; adult weight after emergence and at 20 days old; fecundity; number of egg masses per female; number of eggs per egg mass; egg viability and embrionary period. The parameters of the fertility life table were also evaluated. By the results it was possible to conclude that: caterpillars of D. saccharalis were appropriate for P. nigrispinus development, suggesting the possibility of using these prey in mass rearing of this insect.